2017
DOI: 10.1126/scisignal.aaf4736
|View full text |Cite
|
Sign up to set email alerts
|

De novo phosphorylation and conformational opening of the tyrosine kinase Lck act in concert to initiate T cell receptor signaling

Abstract: The enzymatic activity of the Src family tyrosine kinase p56 (Lck) is tightly controlled by differential phosphorylation of two tyrosine residues, Tyr and Tyr Phosphorylation of Tyr and the conformational opening of Lck are believed to activate the kinase, whereas Tyr phosphorylation is thought to generate a closed, inactive conformation of Lck. We investigated whether the conformation of Lck and its phosphorylation state act in concert to regulate the initiation of T cell receptor (TCR) signaling. With a sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 43 publications
6
68
1
Order By: Relevance
“…These model simulations qualitatively agree with the experimental data. Similar experiments were done by Philipsen et al to test the ERK response given various LCK tyrosine to phenylalanine mutants expressed in LCK negative Jurkat T cells (Philipsen et al, 2017). They found that LCK-Y394F or LCK-Y394F-Y505F essentially eliminated the ERK positive cell population at three minutes, while LCK-Y505F increased the amount of ERK positive cells.…”
Section: Model Is Validated By Independent Experimental Data Setsmentioning
(Expert classified)
See 1 more Smart Citation
“…These model simulations qualitatively agree with the experimental data. Similar experiments were done by Philipsen et al to test the ERK response given various LCK tyrosine to phenylalanine mutants expressed in LCK negative Jurkat T cells (Philipsen et al, 2017). They found that LCK-Y394F or LCK-Y394F-Y505F essentially eliminated the ERK positive cell population at three minutes, while LCK-Y505F increased the amount of ERK positive cells.…”
Section: Model Is Validated By Independent Experimental Data Setsmentioning
(Expert classified)
“…erning these interactions were adapted directly from our previous work . We assume that only LCK phosphorylated on the activating site, Y394, is catalytically active toward the CAR and other downstream proteins in the T cell activation pathway (Philipsen et al, 2017). As our previously published model of CAR tyrosine site phosphorylation only accounts for the catalytic activity of active LCK monophosphorylated at Y394, we assumed that doubly phosphorylated LCK, phosphorylated at the activating site Y394 and the inhibitory site Y505, has a catalytic activity 50x slower than active monophosphorylated LCK.…”
Section: Introductionmentioning
confidence: 99%
“…CD45 expression is required for this basal ζ-chain phosphorylation, presumably to provide for an active pool of Lck (Zikherman et al, 2010). Because a proportion of Lck is active in resting thymocytes and T cells, it has been suggested that changes in the amount of active Lck are not required to initiate TCR signaling, but these findings remain controversial (Ballek et al, 2015; Nika et al, 2010; Philipsen et al, 2017; Stirnweiss et al, 2013). However, it is known that the amount of active Lck in a T cell can determine whether it responds to antigen or not (Manz et al, 2015; Zikherman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Different pools of Lck have been identified, including Lck in the cytoplasm, Lck anchored to the plasma membrane and Lck associated with the co‐receptors CD4 and CD8 . Approximately 40% of Lck is already active (phosphorylated at Y394) in resting T cells and upon TCR engagement the amount of active Lck increases, as seen by Forster resonance energy transfer . In addition, the distribution of Lck to its correct destination may regulate the function of Lck in phosphorylating its substrates .…”
Section: Lckmentioning
confidence: 99%
“…29 Approximately 40% of Lck is already active (phosphorylated at Y394) in resting T cells and upon TCR engagement the amount of active Lck increases, as seen by Forster resonance energy transfer. [30][31][32] In addition, the distribution of Lck to its correct destination may regulate the function of Lck in phosphorylating its substrates. 26 Several lines of evidence have also suggested that initial phosphorylation of the CD3's ITAMs is mediated by free Lck, whereas the co-receptor-associated Lck acts as an adaptor molecule to bring the CD4 or CD8 molecule to the phosphorylated TCR-CD3 complex in a later step.…”
Section: Lckmentioning
confidence: 99%